Arterial stiffness and biochemical profiles in prehypertensive, normotensive, and controlled hypertensive individuals: a cross-sectional study - Vilela-Martin, José Fernando; Minari, Tatiana Palotta; Vieira-da-Silva, Marco A.; Fernandes, Letícia Aparecida Barufi; de Almeida, Marco Aurélio; Lopes, Valquíria da Silva; de Oliveira, Kleber Aparecido; Uyemura, Jessica Rodrigues Roma; Moreno, Heitor; Yugar-Toledo, Juan Carlos; Cosenso-Martin, Luciana Neves (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPrehypertension predisposes individuals to hypertension as well as increased cardiovascular morbidity and mortality. Additionally, central blood pressure and arterial stiffness indices have been linked to higher cardiovascular mortality rates. This study aimed to compare peripheral and central hemodynamic parameters—including blood pressure, pulse wave velocity, and nocturnal dipping—among normotensive, prehypertensive, and controlled hypertensive individuals, alongside the assessment of biochemical variables.MethodsThe study compared clinical and biochemical evaluations and ambulatory blood pressure monitoring (ABPM) results among 47 normotensive (NT), 39 prehypertensive (PH), and 138 controlled hypertensive (CHT) individuals. Peripheral [systolic blood pressure (SBP) and diastolic blood pressure (DBP)] and central hemodynamic [central SBP (cSBP), central DBP (cDBP), and pulse wave velocity (PWV)] parameters were analyzed using ABPM. Central hemodynamic parameters were measured via brachial oscillometry with the Mobil-O-Graph® system.ResultsThe mean ages of NT, PH, and CHT participants were 48.3 ± 10.6, 50.1 ± 9.6, and 57.7 ± 10.9 years, respectively (P < 0.0001). Compared to NT, PH individuals showed higher 24-h systolic blood pressure (130.2 ± 5.6 vs. 118.7 ± 4.9 mmHg; P < 0.0001), central systolic pressure (125.4 ± 6.1 vs. 113.2 ± 5.3 mmHg; P < 0.0001), and pulse wave velocity (8.2 ± 1.1 vs. 7.6 ± 0.9 m/s; P = 0.01). Triglycerides levels were significantly higher in PH (178 ± 42 mg/dL) than in NT (132 ± 36 mg/dL; P = 0.0002) and lower than in CHT (192 ± 47 mg/dL; P = 0.03). Glycemia, LDL cholesterol, and total cholesterol also differed significantly between PH and CHT groups (P < 0.001).ConclusionPrehypertensive individuals exhibited higher peripheral and central blood pressures compared to normotensive individuals but lower levels than controlled hypertensive patients during all three periods (24-h, wake, and sleep). These findings suggest that functional and structural alterations predisposing individuals to hypertension are already present in the prehypertensive stage.